2016
DOI: 10.1016/j.jmoldx.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive Pharmacogenomic Testing for Precision Medicine

Abstract: Significant barriers, such as lack of professional guidelines, specialized training for interpretation of pharmacogenomics (PGx) data, and insufficient evidence to support clinical utility, prevent preemptive PGx testing from being widely clinically implemented. The current study, as a pilot project for the Right Drug, Right Dose, Right Time-Using Genomic Data to Individualize Treatment Protocol, was designed to evaluate the impact of preemptive PGx and to optimize the workflow in the clinic setting. We used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
93
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(114 citation statements)
references
References 11 publications
10
93
0
Order By: Relevance
“…The method used to predict drug metabolizer phenotype for CYP2D6 included intermediate phenotype categories (EM to UM, IM to EM and PM to IM) according to a recent paper and was summarized in S1 Fig. [23]. …”
Section: Methodsmentioning
confidence: 99%
“…The method used to predict drug metabolizer phenotype for CYP2D6 included intermediate phenotype categories (EM to UM, IM to EM and PM to IM) according to a recent paper and was summarized in S1 Fig. [23]. …”
Section: Methodsmentioning
confidence: 99%
“…Following on from this, in a very recent publication revealed that in this RIGHT cohort of 1,013 subjects, tested for five well-characterized pharmacogenomic genes (CYP2D6, CYP2C19, SLCO1B1, CYP2C9, and VKORC1), 99% of the participants carried a pharmacogenomics variant that could impact on the metabolism, effectiveness and sideeffect profile of a given drug [37,38]. It will be very interesting to see how a longitudinal follow up from this "RIGHT" initiative will impact on the appropriate prescribing of therapeutics.…”
Section: Pharmacogenomics and Polypharmacymentioning
confidence: 96%
“…The prediction model included age, sex, race, and 6 chronic diseases categorised by the Clinical Classifications Software for International Classification of Diseases, Ninth Revision codes (dyslipidemia, diabetes, peripheral atherosclerosis, disease of the blood-forming organs, coronary atherosclerosis and other heart diseases, and hypertension). Pre-emptive pharmacogenomic testing of this group included CYP2D6 genotyping and targeted sequencing of 84 pharmacogenomes that had FDA warnings for drug interactions.The genomic results were entered into the individuals' electronic medical record (EMR) and if a drug was prescribed for the individual potential patient-specific, drug-gene interactions would be flagged.Following on from this, in a very recent publication revealed that in this RIGHT cohort of 1,013 subjects, tested for five well-characterized pharmacogenomic genes (CYP2D6, CYP2C19, SLCO1B1, CYP2C9, and VKORC1), 99% of the participants carried a pharmacogenomics variant that could impact on the metabolism, effectiveness and sideeffect profile of a given drug [37,38]. It will be very interesting to see how a longitudinal follow up from this "RIGHT" initiative will impact on the appropriate prescribing of therapeutics.…”
mentioning
confidence: 96%
“…For example, among those original 1013 subjects, if only five “common” pharmacogenes out of the 84 sequenced were included, 99.1% of the subjects had at least one actionable variant in at least one of those five genes—with many subjects having clinically actionable variant sequences in several of the five genes. 31 This observation explains why, at the beginning of this overview, we made the statement that “pharmacogenomics is the aspect of clinical genomics that will almost certainly see the earliest and broadest clinical implementation—with the potential to eventually touch the care of every patient everywhere”. To follow up on those initial RIGHT study results, the Mayo Clinic Center for Individualized Medicine, in collaboration with the Baylor Human Genome Sequencing Center, is currently moving beyond the original 1013 biobank samples to consent and sequence 10,000 additional Mayo Biobank participants for a “RIGHT 10K” study designed to test the hypothesis that having preemptive pharmacogenomic information in the EHR might result in cost-effective health benefits for the patients involved—helping them to avoid adverse drug reactions and obtain maximum efficacy from drug therapy.…”
Section: Pharmacogenomics: Clinical Implementationmentioning
confidence: 99%